Managing dementia in rural Nigeria: feasibility of cognitive stimulation therapy and exploration of clinical improvements. (3rd October 2019) - Olakehinde, Olaide; Adebiyi, Akinpelu; Siwoku, Akeem; Mkenda, Sarah; Paddick, Stella-Maria; Gray, William K.; Walker, Richard W.; Dotchin, Catherine L.; Mushi, Declare; Ogunniyi, Adesola
Abstract: Objectives: We investigated the feasibility and clinical impact of a psychosocial intervention, Cognitive Stimulation Therapy (CST), to help manage dementia in a rural setting in Nigeria. Method: People with dementia were identified from a prevalence study in Lalupon in the south-west of Nigeria. Prior to this feasibility study CST was adapted for the setting and pilot by our team. Fourteen sessions of CST were provided over a 7-week period by a trained nurse specialist and occupational therapist. Change in quality of life was the main outcome. Results: Nine people were enrolled in CST. Significant improvements in cognitive function, quality of life (physical, psychosocial and environmental domains), physical function, neuro-psychiatric symptoms and carer burden were seen. Conclusions: CST appears to be feasible in this setting, although adaptation for low literacy levels, uncorrected visual and hearing impairment and work and social practices is needed. The clinical improvements seen were encouraging.